Health care seeking behaviour of pulmonary tuberculosis patients in Jabalpur district, Madhya Pradesh - Sahu, Rupesh; Verma, Prashant; Kasar, Pradeep K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Successful tuberculosis control requires specific behaviors from patients and health providers. Therefore, understanding behaviors is fundamental to design interventions to strengthen tuberculosis control programs, including communication interventions. The aim of this study was to assess the healthcare-seeking behavior of pulmonary tuberculosis (PTB) patients in Jabalpur district. Methods: Cross-sectional study was conducted among category I new sputum positive PTB patients identified from nine designated microscopy centres from November 2013 to October 2014. Calculated sample size of 135 with a multistage random sampling method was used. Student’s t-test and Chi-square test were used along with descriptive statistics. Results: Mean age of patients was 33.87 (14.3) years, males constituted 66.7%, 72.5% patients belonged to below class IV socioeconomic status. Cough was experienced by 91.1% subjects, followed by fever (69.6%). First action was consulting a health care provider (HCP) in 41.5% followed by self-medication (21.5%). It took two attempts for 76% of patients to reach a formal health care provider. Private health care providers were consulted as first choice among HCPs by 86.7% patients, initial diagnosis was made by them in 25.9% cases. Sixty-three percent of patients were not satisfied with care at government hospitals, 41.5% had not heard of tuberculosis before their diagnosis, 59.5% of patients got information about tuberculosis from their relatives suffering from it. Conclusions: Cough is the most common and earliest symptom responsible for seeking care in pulmonary tuberculosis. Government health facilities contribute maximum to diagnosis but private health facility is the first choice for initial consultation. Patients’ perception of suggestive symptoms needs to be changed.